2013
DOI: 10.1136/bmjqs-2012-001774
|View full text |Cite
|
Sign up to set email alerts
|

Reducing unnecessary urinary catheter use and other strategies to prevent catheter-associated urinary tract infection: an integrative review

Abstract: BackgroundCatheter-associated urinary tract infections (CAUTI) are costly, common and often preventable by reducing unnecessary urinary catheter (UC) use.MethodsTo summarise interventions to reduce UC use and CAUTIs, we updated a prior systematic review (through October 2012), and a meta-analysis regarding interventions prompting UC removal by reminders or stop orders. A narrative review summarises other CAUTI prevention strategies including aseptic insertion, catheter maintenance, antimicrobial UCs, and bladd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
336
2
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 335 publications
(356 citation statements)
references
References 68 publications
5
336
2
13
Order By: Relevance
“…Assim, sempre que possível, a inserção do CVD deve ser questionada quando as possibilidades de ser substituída por algum destes meios. 1,[8][9][10][13][14][15] Portanto, a conformidade encontrada no Indicador 1 para o setor da Emergência não a exime da necessidade de estabelecimento de ações de controle para ITU-RC, assim como para o setor do CTI que não obteve conformidade neste Indicador.…”
Section: Discussionunclassified
“…Assim, sempre que possível, a inserção do CVD deve ser questionada quando as possibilidades de ser substituída por algum destes meios. 1,[8][9][10][13][14][15] Portanto, a conformidade encontrada no Indicador 1 para o setor da Emergência não a exime da necessidade de estabelecimento de ações de controle para ITU-RC, assim como para o setor do CTI que não obteve conformidade neste Indicador.…”
Section: Discussionunclassified
“…The lack of qualified change champions within the wards to assist managers to implement changes also affected our choice of method. Using electronic alerts, which can assist in reducing CAUTIs [6,12,13] and allow easily accessible audits, was not an option because the hospital's electronic documentation system did not offer such features. Despite the decrease in the proportion of inpatient days with a catheter, the ratio was still quite high (41%) at T2 compared to some other studies [27], where it has been reported to be as low as 10% [28].…”
Section: Discussionmentioning
confidence: 99%
“…Diverse interventions that focus on limiting catheter use and on their prompt removal may significantly reduce CAUTIs [3, [9][10][11]. Education of nursing staff, electronic reminders aimed at reducing the duration of invasive devices [6,12], such as automatic stop orders [13], and the use of nurses specially trained to lead implementation projects (change champions) [12] have proved to be effective in changing practice and reducing CAUTIs [14].…”
Section: Introductionmentioning
confidence: 99%
“…Effective perineal protocols require nursing management, quality and supply chain acceptance and commitment for each institution. To date, only two methodologies have consistently proven to be effective in reducing CAUTI rates; implementing closed catheter systems and early removal of the catheter [7]. Scheduled cleansing of the catheter and urethral meatus, referred to as catheter care and maintenance, deserves scrutiny when designing a program to prevent CAUTI.…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrates the soap and water care is beneficial as an initial step in a protocol to reduce macroscopic debris and prepare the perineum for application of other agents that may be additive in their effect on reducing CAUTI. Less than expected results from all products and methodology point to the need for quality improvement oversight and implementation for evidenced based practice guidelines including comprehensive education across all departments [11][12][13][14] …”
Section: Introductionmentioning
confidence: 99%